Wetland Potential-Based PBL: Developing Creative Thinking and Entrepreneurship Skills of Vocational High School Students on the Topic of Static Fluid - Ikhwan Khairu Sadiqin; Akhmad Zulkarnain (Universitas Lambung Mangkurat, 2026)
The creative thinking and entrepreneurship skills of Vocational High School (SMK) students are often considered less applicable to industrial needs. This is partly due to the lack of relevant learning models that utilize local potential. This study aims to analyze the profile of students' creative thinking and entrepreneurship skills through the implementation of a Project-Based Learning (PjBL) model based on wetland potential on the topic of static fluid. The method employed in this research is quantitative descriptive. The research subjects were Class X SMK students in Banjarmasin. Data were collected using creative thinking test instruments and entrepreneurship skill observation sheets, then analyzed using descriptive statistics. The results showed that the students' competence profile was in the